PELATIHAN DAN PENDAMPINGAN PENINGKATAN KUALITAS PELAYANAN WISATA DI DESA KARYAMEKAR, KABUPATEN GARUT - Susanto Susanto; Ika Baskara; Sri Purwati; Ai Nunung; Sophiyanto Wuryan (JURNAL ABDIMAS PLJ, 2025)
Karyamekar Village, Garut Regency, has significant potential in natural and cultural tourism; however, the quality of tourism services provided by the community has not been optimal. The main problems include limited knowledge and skills in providing services, low understanding of tourism service standards, and insufficient guidance in managing village tourism destinations. This community service program aims to improve tourism service quality through training and direct mentoring for the community and tourism managers. The methods include participatory training, material delivery, discussions, service simulations, and field mentoring. The training focused on service excellence, effective communication, service ethics, cleanliness and comfort of tourist destinations, and the application of Sapta Pesona. The results indicate increased  knowledge,  skills,  and  awareness  of  the  community  in  delivering  professional tourism services, which positively impact tourist satisfaction and support sustainable village tourism development.